Synapses, synaptic activity and intraneuronal Aβ in Alzheimer's disease - Tampellini, Davide; Gouras, Gunnar K. (Frontiers in Aging Neuroscience, 2010)
β-amyloid peptide accumulation plays a central role in the pathogenesis of Alzheimer’s disease. Aberrant β-amyloid buildup in the brain has been shown to be present both in the extracellular space and within neurons. Synapses are important targets of β-amyloid, and alterations in synapses better correlate with cognitive impairment than amyloid plaques or neurofibrillary tangles. The link between β-amyloid and synapses became even tighter when it was discovered that β-amyloid accumulates within synapses and that synaptic activity modulates β-amyloid secretion. Currently, a central question in Alzheimer’s disease research is what role synaptic activity plays in the disease process, and how specifically β-amyloid is involved in the synaptic dysfunction that characterizes the disease.